Valor agregado e desenvolvimento sustentável: o caso das agroindústrias rurais no município de Cerro Largo - Pieniz, Felipe Guerim (2021)
Work is the main category of analysis to understand human behavior. Considering that from a macroeconomic point of view the added value corresponds to the monetary equivalent of the socially necessary working time applied in production, by the principle of totality, the added value (generation and distribution) becomes the main category of analysis of the development of the social being. The same applies to the microeconomic analysis, carried out this research, even with the distortions of capitalism system. As for rural development, considering society as an open system, it is clear that even in the face of the significant increase in Brazilian agricultural production, in recent years the contradictions of rural activities in their social, economic and environmental aspects have been aggravated. In the approach of historical materialism, the root of the problem lies in the capitalist production system, whose logic is based on a supposedly “free” market. From the ecosocialist perspective, there is a need to reduce the contradictions of the system by favoring peasant agriculture over capitalist agriculture. For, under certain conditions, compared to the capitalist system, the peasant production system manages to generate more added value per area with techniques more consistent with the dynamics of ecosystems. As an alternative to enable the social reproduction of peasant production units is the activity of rural agroindustry, an option to diversify the activities of family farmers that makes it possible to increase income within the production unit without the need to increase the area of the establishment. This work sought by the method Analysis-diagnosis of Agrarian Systems, analyze the rural agroindustries as an alternative to the generation of value added in a sustainable development perspective. The study was carried out in the municipality of Cerro Largo where the method had already been used to characterize agriculture in the region without considering establishments with rural agroindustries. The results obtained demonstrate that rural agroindustry contribute significantly to the generation of added value in the production units, as well as to the generation of income for farmers. The analysis found that since the beginning of the twentieth century activities characterized as rural agroindustry have been performed to meet subsistence consumption in most rural establishments in the municipality, a favorable situation for new farmers to seek to specialize in order to commercialize production. However, for more farmers to be able to carry out the activity in their production units, a structure with public financing policies, price guarantee (demand) and technical assistance is necessary. Thus, in view of the findings of the survey were two strategic lines proposed for the development of rural agroindustries in the municipality of Cerro Largo: demands generation of rural agroindustries products and targeted technical assistance. The two proposed lines meet the need to strengthen peasant agriculture.